An Observational Study of Dialogue about Uncertainty in Clinician-Family Counseling Conversations Following Prenatal Diagnosis of Complex Congenital Heart Disease - Kelly W. Harris; Kelsey Schweiberger; Ann Kavanaugh-McHugh; Robert M. Arnold; Jessica Merlin; Judy C. Chang; Nadine A. Kasparian (Elsevier, 2024)
Objective: Families who receive a prenatal diagnosis of complex congenital heart disease (cCHD) often experience severe psychological distress and identify uncertainty as a key source of that distress. This study examined clinician-family conversations during initial fetal cardiology consultations to identify the topics of uncertainty discussed. Methods: In this observational, qualitative study, initial fetal cardiology consultations were audio-recorded, transcribed verbatim, and coded by two independent coders. A codebook was inductively and deductively developed and applied. This content analysis focused on uncertainty-related codes and associated themes. Results: During 19 consultations including five clinicians, 13 different cardiac diagnoses were discussed (seven with high mortality risk). Median consultation length was 37 min (IQR: 26-51), with only 11% of words spoken by families. On average, 51% of total words spoken focused on uncertainty in relation to cardiac diagnosis, etiology, comorbidities, prognosis, childbirth, therapeutics, and logistics. Family-initiated discussion on uncertainty largely focused on childbirth and pregnancy and postpartum logistics. Conclusions: Half of dialogue within initial fetal cardiology encounters discussed uncertainty surrounding prenatally diagnosed cCHD. Parent and clinician perspectives should be gathered on the essential content and optimal delivery of uncertainty-related topics. Innovation: This study is conceptually and methodologically innovative as one of the first to examine audio-recorded dialogue between fetal cardiology clinicians and families.